2012
DOI: 10.1016/j.pain.2011.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of rodent neuropathic pain by an orally active peptide, RAP-103, which potently blocks CCR2- and CCR5-mediated monocyte chemotaxis and inflammation

Abstract: Chemokine signaling is important in neuropathic pain, with microglial cells expressing CCR2 playing a well-established key role. DAPTA, a HIV gp120-derived CCR5 entry inhibitor, has been shown to inhibit CCR5-mediated monocyte migration and to attenuate neuroinflammation. We report here that as a stabilized analog of DAPTA, the short peptide RAP-103 exhibits potent antagonism for both CCR2 (half maximal inhibitory concentration [IC50] 4.2 pM) and CCR5 (IC50 0.18 pM) in monocyte chemotaxis. Oral administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 31 publications
4
57
0
Order By: Relevance
“…Similar results were seen in our earlier study showing that knockdown of CCR5 in the SCN using siRNA prevented both allodynia and hyperalgesia (Kiguchi et al, 2010b). Consistent with our findings, recent report showed that neuropathic pain after nerve ligation were not elicited in CCR5 knockout mice (Padi et al, 2012). These lines of evidence confirm that MIP-1b mainly participates in tactile allodynia after nerve injury.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were seen in our earlier study showing that knockdown of CCR5 in the SCN using siRNA prevented both allodynia and hyperalgesia (Kiguchi et al, 2010b). Consistent with our findings, recent report showed that neuropathic pain after nerve ligation were not elicited in CCR5 knockout mice (Padi et al, 2012). These lines of evidence confirm that MIP-1b mainly participates in tactile allodynia after nerve injury.…”
Section: Discussionsupporting
confidence: 93%
“…Of the 44 genes in the GO Axon Extension and GO Regulation of Axonogenesis overlap set (Supplemental Table 7), a number have been implicated in neuropathy, including hereditary neuropathy genes ( MAP1B 46 , NGF 47 , FXN 48 ), genes with variants or expression signatures associated with diabetic or HIV-induced peripheral neuropathy ( APOE 49, 50 , MAPT 51 , CDH4 51 ), genes involved in neurological pain pathways ( MT3 52 , TRPV2 53 , CCR5 54 , CXCL12 55 ), and genes involved in response to or repair/prevention of peripheral nerve damage ( RYK 56 , SLIT1 57 , NTRK3 58 , NGF 59, 60 , TRPV2 53 , NTN1 61 , NDEL1 62 ). The majority (38) of these 44 genes fall in the GO term Regulation of Axon Extension (GO 0030516), which is a subset of both GO Regulation of Axonogenesis and GO Axon Extension.…”
Section: Discussionmentioning
confidence: 99%
“…To potentially increase the efficacy of chemokine antagonism it might be beneficial to simultaneously target several chemokine receptors. Indeed the dual CCR2/CCR5 peptide antagonist RAP-103 (which was orally active) effectively reduced neuropathic pain and inhibit CCR2- and CCR5-mediated monocyte chemotaxis and inflammation in rodents 94 .…”
Section: Chemokines: Mediators Of Neuron–glial Interactionsmentioning
confidence: 99%